Preventive Methods for Coastal Protection 2013
DOI: 10.1007/978-3-319-00440-2_8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Tuning of Model Trajectories and Spreading Rates in the Baltic Sea Using Surface Drifter Observations

Abstract: Results from experiments with surface drifters in the Baltic Sea in 2010-2011 are presented and discussed. In a first experiment, 12 SVP-B (Surface Velocity Program, with Barometer) drifters with a drogue at 12-18 m depth were deployed in the Baltic Sea. In a second experiment, shallow drifters extending to a depth of 1.5 m were deployed in the Gulf of Finland. Results from the SVP-B drifter experiment are compared to results from a regional ocean model and a trajectory code. Differences between the observed S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…The model forecast fails to ever reach a crossover time for the entire span of the available prediction. During the study period the average decorrelation times of the drifter velocities was found to be 1.2 days (not shown) in approximate agreement with Poulain et al (1996), LaCasce (2008), Döös et al (2013), and Lumpkin and Johnson (2013). This time scale is very similar to the e-folding time scale of persistence (black line in Figure 2a).…”
Section: Global Summarysupporting
confidence: 64%
“…The model forecast fails to ever reach a crossover time for the entire span of the available prediction. During the study period the average decorrelation times of the drifter velocities was found to be 1.2 days (not shown) in approximate agreement with Poulain et al (1996), LaCasce (2008), Döös et al (2013), and Lumpkin and Johnson (2013). This time scale is very similar to the e-folding time scale of persistence (black line in Figure 2a).…”
Section: Global Summarysupporting
confidence: 64%
“…Residence times of litter at the sea surface would not necessarily be an appropriate choice, considering high uncertainty of particle trajectories integrated over very long periods. Kjellsson et al (2013) exemplified this uncertainty for real drifters in the Baltic Sea. We feel that for our application in the North Sea, 90 day integration time was a reasonable choice.…”
Section: Discussionmentioning
confidence: 89%
“…This is due to the fact that oceanic advection shows chaotic behavior: Small changes in the initial conditions (in time and space) may lead to different system behavior. Kjellsson et al (2013) demonstrated this by analyzing observed drifter trajectories in the Baltic Sea. Within the first 20 days of drift, two drifters which were started close to each other separated by up to 40 km.…”
Section: Setup Of Experiments and Evaluation Methodsmentioning
confidence: 98%
“…Research on hydrodynamic models of reservoir surface waters is conducted in many research centers. Findings on the distribution of surface drifters in the Baltic Sea in 2010 and 2011 are described in (Kjellsson and Döös, 2011). The authors compare drifter trajectories with trajectories generated by a numerical model using fields, i.e., wind forcing with parameterization of gusty winds, from a regional ocean model.…”
Section: Literature Review and Discussionmentioning
confidence: 99%